Treatment Outcomes for Maple Syrup Urine Disease Detected by Newborn Screening - Mengler, Katharina; Garbade, Sven; Gleich, Florian; Thimm, Eva; May, Petra; Lindner, Martin; Lüsebrink, Natalia; Marquardt, Thorsten; Hübner, Vanessa; Krämer, Johannes; Neugebauer, Julia; Beblo, Skadi; et al. (Pediatrics, 2024)
Maple syrup urine disease (MSUD), a life-threatening metabolic disorder, is included in newborn screening (NBS) programs worldwide. The study aims to evaluate the impact of NBS on the long-term outcome of MSUD patients.We performed a prospective, national, multicenter, observational study.In the studied NBS cohort (N = 33; 22 classic MSUD [cMSUD], 11 variant MSUD [vMSUD]; median age at last visit 10.4 years), 32 (97%) patients survived, 58% of them had normal cognitive functions (median IQ 87). Initial peak leucine increased linearly with age in cMSUD (median: 1712 µmol/L), but not in vMSUD. Global IQ correlated inversely with the initial peak leucine concentration (P = .04; β = -0.0081) and the frequency of decompensations (P = .02; β = -9.133). A cluster analysis identified 2 subgroups differing in their long-term metabolic control (median leucine concentration: 162 vs 278 µmol/L; P < .001). In cMSUD, lower leucine concentrations were associated with a higher IQ (95.5 vs 80; P = .008). Liver transplantation (median age 5.8 years) was not associated with better cognitive outcome. NBS is highly sensitive for cMSUD, but vMSUD might be missed (N = 2 missed by NBS).NBS and the early start of treatment improve survival and long-term outcome in individuals with cMSUD. Disease severity is an important modifier of outcome; however, the time to NBS report and the quality of long-term metabolic control had an independent impact on cognitive outcome, highlighting the importance of an early diagnosis and the quality of treatment.